DIAGNOSIS AND TREATMENT OF RENAL ARTERIAL HYPERTENSION IN PEDIATRIC PRACTICE - Gonchar, M.O.; Alenina, I.S.; Senatorova, G.S. (World of Medicine and Biology, 2021)
The article considers the problem of renal arterial hypertension as one of the frequent manifestations of secondary arterial hypertension in childhood, which contributes to an increase in the rate of disease progression. Symptoms of renal hypertension are due to the level of blood pressure, manifestations of cardiovascular disease and the presence of proteinuria. Blood pressure indicators were analyzed in 86 children with chronic kidney disease. According to the results of diurnal monitoring of blood pressure in 58.1±5.3 % (50/86) children, violations of the circadian rhythm of daily fluctuations in blood pressure were revealed. Renal arterial hypertension was diagnosed in 41.8±5.3 % (36/86) children. For doctors who observe pediatric patients, especially with kidney pathology, approaches to non-pharmacological and pharmaceutical treatment of renal hypertension in children are offered. These include physical activity correction, nutrition in accordance with the child’s basic age needs, in combination with the appointment of renoprotective therapy. For initial treatment, it is recommended to use drugs from the group of inhibitors of angiotensin converting enzyme and blockers of angiotensin receptors.
Keywords: renal arterial hypertension; children; diagnosis; renoprotection